Adenine and Thymine Effect on Quartz Dissolution at Different Artificial Seawaters - Zaia, Dimas Augusto Morozin; Pereira, Rodrigo de Carvalho; Samulewski, Rafael Block (Orbital: The Electronic Journal of Chemistry, 2018)
According to Bernal (1951) minerals may have played important roles in the origin of life such as: protect biomolecules against degradation by UV radiation or hydrolysis, pre-concentrate biomolecules from prebiotic seas and formation of polymers. Today quartz is widely distributed on Earth as well as was widely distributed on the prebiotic Earth. There are several works showing the quartz dissolution, this work shows for the first time, quartz dissolution under prebiotic chemistry conditions. The experiments were carried out with and without adenine and thymine dissolved in several artificial seawaters, distilled water and alkaline distilled water (pH = 11.0). It should be noted that seawater 4.0 Ga resembles the major cations and anions of the sea of the prebiotic Earth. The quantification of dissolved quartz in different seawater, the measurement of pH and of conductivity were performed daily for a 35 day period, at a controlled temperature (30 °C). The dissolution was dependent of water salinity and especially of pH. Depending on the artificial seawater, adenine and thymine can either accelerate the quartz dissolution or protect it. DOI: http://dx.doi.org/10.17807/orbital.v10i6.1152\